2012
DOI: 10.1016/j.susc.2012.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz surfoluminescence

Abstract: The cleaving of a solid to form two new surfaces may result in the emission of light. Conventional mechanoluminescence involves the transfer of charge between the two surfaces. We now demonstrate that the ultra-fast separation of charge within a newly-formed surface will lead to the emission of electromagnetic radiation. In contrast to the visible light previously observed and modeled, the intra-surface radiation contains terahertz frequencies. This new mechanism -named here surfoluminescence -introduces a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A terahertz source generates a wide range of radiation [59]. R. A. Lewis [60] presents six types of THz sources which include thermal [61] [62], vacuum electronic [63]- [65], solid-state electronic [66] [67], lasers [68] [69], sources pumped by lasers (including continuous [70] [71], pulsed [72] [73]) and mechanical excitation sources [74] [75].…”
Section: A the Thz Sourcesmentioning
confidence: 99%
“…A terahertz source generates a wide range of radiation [59]. R. A. Lewis [60] presents six types of THz sources which include thermal [61] [62], vacuum electronic [63]- [65], solid-state electronic [66] [67], lasers [68] [69], sources pumped by lasers (including continuous [70] [71], pulsed [72] [73]) and mechanical excitation sources [74] [75].…”
Section: A the Thz Sourcesmentioning
confidence: 99%
“…R. A. Lewis list six main types of terahertz sources [6]. These include thermal [7,8], vacuum electronic [9][10][11], solid-state electronic [12,13], lasers [14,15], sources pumped by lasers [16,17], and mechanical-excitation types of terahertz radiation sources [18,19]. Sources pumped by lasers employ either continuous or pulsed lasers.…”
Section: Generation and Detection Of Terahertz Radiationmentioning
confidence: 99%
“…In this paper we examine a simple method to implement, optical excitation of bare semiconductor surfaces. We have previously reported that surface formation itself can give rise to terahertz radiation (9). In this paper we compare and contrast the emission from InAs (10,11) and from GaAs (12) under optical excitation by ultrashort pulses.…”
Section: Introductionmentioning
confidence: 97%